2021
DOI: 10.3390/ijerph18041935
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Health Risk Assessment (AP-HRA), Principles and Applications

Abstract: Air pollution is a major public health problem. A significant number of epidemiological studies have found a correlation between air quality and a wide variety of adverse health impacts emphasizing a considerable role of air pollution in the disease burden in the general population ranging from subclinical effects to premature death. Health risk assessment of air quality can play a key role at individual and global health promotion and disease prevention levels. The Air Pollution Health Risk Assessment (AP-HRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 117 publications
(69 reference statements)
0
21
0
1
Order By: Relevance
“…For example, haze often occurs in Zhejiang Province in winter and reduces visibility, greatly limiting people's travel. Additionally, haze also harms the health of residents, and long-term inhalation of pollutant particles induces respiratory tract infections and other related diseases [23][24][25][26]. In addition, air pollution will affect the supply of labor through the mechanism of residents' happiness [37,38,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, haze often occurs in Zhejiang Province in winter and reduces visibility, greatly limiting people's travel. Additionally, haze also harms the health of residents, and long-term inhalation of pollutant particles induces respiratory tract infections and other related diseases [23][24][25][26]. In addition, air pollution will affect the supply of labor through the mechanism of residents' happiness [37,38,43].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased air quality increases the prevalence of respiratory diseases, mortality from malignant lung cancers, and the incidence of neurological, cardiac, and neurovascular diseases [21]. The characteristics of the premature deaths caused by PM2.5 (Fine Particulate Matters) in the different types of cities in China provide evidence [5,22,23]. Luo et al (2018) concluded that the mortality rate in areas with better air quality was much lower than that in areas with high levels of pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The table on the left of the figure illustrates the output data generated from the NFT-MEP model with five classes according to T-AQI. The first column shows the time in a 24-h cycle and the second column is the PM concentration (1)(2)(3)(4)(5). The table on the right of the figure illustrates an example of the six hours before the desired time dataset.…”
Section: New Informative Features Generationmentioning
confidence: 99%
“…Air pollution is a major problem in public health that increases health impacts on both the cardiovascular and respiratory systems in humans [1]. There are many important air pollutants, including ground-level ozone (O 3 ), carbon monoxide (CO), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), and particulate matter (PM), announced by the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…The risks posed by air pollution lead to side effects such as poor public health and increased mortality [1]. According to the World Health Organization (WHO), 4.2 million people die each year from outdoor air pollution and 3.8 million people die from indoor air pollution [2]. The premature mortality rate from air pollution is expected to double by 2050, which is recognized as the world's most serious environmental and health threat [3].…”
Section: Introductionmentioning
confidence: 99%